The Brucella abortus two-component system response regulator BvrR binds to three DNA regulatory boxes in the upstream region of omp25 - Castillo-Zeledón, Amanda; Rivas-Solano, Olga; Villalta-Romero, Fabián; Gómez-Espinoza, Olman; Moreno, Edgardo; Chaves-Olarte, Esteban; Guzmán-Verri, Caterina (Frontiers in Microbiology, 2023)
B. abortus is a facultative extracellular-intracellular bacterial zoonotic pathogen worldwide. It is also a major cause of abortion in bovines generating economic losses. The two-component regulatory system BvrR/BvrS modulates the expression of genes required to transition from extracellular to intracellular lifestyles. However, few regulatory regions from BvrR direct target genes have been studied. Here, we characterized the regulatory region of omp25, a gene encoding an outer membrane protein and positively regulated by TCS BvrR/BvrS. By omp25-lacZ reporter fusions and β-galactosidase activity assays, we found that the region between -262 to +127 is necessary for transcriptional activity, particularly a 111 bp long fragment, located from -262 to -152. In addition, we demonstrated the binding of P-BvrR to three sites within the -140 to +1 region. Two of these sites were delimited between -18 to +1 and -99 to -76 by DNase I footprinting and called DNA regulatory boxes 1 and 2, respectively. The third binding site (box 3) was delimited from -140 to -122 by combining EMSA and fluorescence anisotropy results. A molecular docking analysis with HDOCK predicted BvrR-DNA interactions between 11, 13, and 12 amino acids residues-nucleotide pairs in boxes 1, 2, and 3, respectively. A manual sequence alignment of the three regulatory boxes revealed the presence of inverted and non-inverted repeats of five to eight nucleotides partially matching DNA binding motifs previously described for BvrR. We propose that P-BvrR binds directly to up to three regulatory boxes and probably interacts with other transcription factors to regulate omp25 expression. This gene regulation model could apply to other BvrR target genes and to orthologs of the TCS BvrR/BvrS and Omp25 in phylogenetically closed Rhizobiales.